A abstração em Tomás de Aquino: um estudo a partir da primeira parte da Suma de teologia - Teixeira, Lucas Pereira (2021)
According to Thomas Aquinas, human intellect understands material things by abstracting intelligible species from phantasms. Among other things, this thesis expresses the dependence that understanding has on operation of the senses, since phantasms are usually defined by him as likenesses of particular things existing in bodily organs. Furthermore, only the senses properly apprehend particulars. But, if intellectual cognition is distinguished by being immaterial, unchangeable, and universal, then, under what conditions is it possible to have intellectual cognition of bodies, which are material, changeable and particular? Aquinas’ account on abstraction of intelligible species from phantasms seems to be an answer to this kind of question. However, it remains to be inquired the precise conceptual and argumentative framework in which this answer arises. Thus, this master’s dissertation aims at analyzing and interpreting the Aquinas’ account on the operation of abstraction of the human intellect. Methodologically, I shall proceed in two ways: particularly, by considering the subject presentation found in articles one and two of question eighty-five of the first part of the Summa Theologiae; more widely, by considering some textual passages from questions seventy-five to seventy-nine, and from questions eighty-four to eighty-nine — still from the same part of the work —, but also by taking into account some textual passages from others works by Thomas Aquinas